Boron phosphide microwires based on-chip electrocatalytic oxygen evolution microdevice - Hongwei Su; Qing Guo; Hongtao Li; Alei Li; Yunlei Zhong; Xu Zhang; Lin Geng; Shuai Liu; Liuqi Dong; Xiaohang Pan; Lin Wang; Lixing Kang (iScience)
Summary: Developing low-cost, high-performance metal-free electrocatalysts is crucial for sustainable oxygen evolution reactions (OERs) in alkaline media. Here, we synthesized ultra-long boron phosphide (BP) microwires along the [111] crystal axis with high yield. By controlling temperature and adding Ni, we identified Ni’s role as a flux and transport agent, optimizing BP microwires at 1050°C. Electrical property and band structure analysis revealed BP as a one-dimensional p-type semiconductor with a wide band gap. We constructed an on-chip electrocatalytic microdevice using individual BP microwires to evaluate OER performance. In 1M NaOH, the BP electrode achieved 50 mA cm−2 at an overpotential of 320 mV, outperforming other boron-based catalysts. Additionally, the nanocatalyst exhibited a low Tafel value (88 mV·dec−1) and excellent stability. This study offers valuable insights for developing future electrocatalysts and electrochemical reaction models.